2004
DOI: 10.1063/1.1703530
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent β-convection in rapidly rotating spherical shells

Abstract: A quasi-geostrophic, or ␤, model of nonlinear thermal convection in rapidly rotating spherical fluid shells is investigated. We study time dependent instabilities for a range of Rayleigh number and Ekman number with a Prandtl number set to the unity. Above the onset of convection, increasing the Rayleigh number for a given Ekman number, we reproduce the sequence of bifurcations described by Busse ͓Phys. Fluids 14, 1301 ͑2002͔͒ for the three-dimensional case: A first transition results in vacillating flow; a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…With σ = 1 and for weak supercritical conditions the flow is strongly oscillatory, displaying an intermittent pattern [8]. The sequence of transitions observed in the full three-dimensional simulations of [36] was reproduced in [26] by using the quasi-geostrophic approximation. The authors found that, as the Ekman number is decreased, the transition to oscillatory convection occurs for marginally supercritical Rayleigh numbers.…”
mentioning
confidence: 80%
“…With σ = 1 and for weak supercritical conditions the flow is strongly oscillatory, displaying an intermittent pattern [8]. The sequence of transitions observed in the full three-dimensional simulations of [36] was reproduced in [26] by using the quasi-geostrophic approximation. The authors found that, as the Ekman number is decreased, the transition to oscillatory convection occurs for marginally supercritical Rayleigh numbers.…”
mentioning
confidence: 80%
“…Morin & Dormy noted that the critical value of required to set the vacillation instability becomes quite small when E diminishes, and that the vacillation instability then transforms into a pulsed instability leading to relaxation oscillations (like the ones shown in the figure 8 of Morin & Dormy 2004). It would be interesting to run new simulations of this kind in a clearly subcritical case.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…One should be aware that, at finite values of E, the thermal Rossby waves are typically subject to a secondary vacillation instability at rather small values of , as shown, for instance, by the numerical simulations of Tilgner & Busse (1997) with a three-dimensional model, and by Cole (2004), Morin & Dormy (2004) with cylindrical QG models. Morin & Dormy noted that the critical value of required to set the vacillation instability becomes quite small when E diminishes, and that the vacillation instability then transforms into a pulsed instability leading to relaxation oscillations (like the ones shown in the figure 8 of Morin & Dormy 2004).…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With magnetic effects, we can imagine very complicated situations. Oscillation properties can drastically change, even disappear (Grote & Busse 2000;Morin & Dormy 2004).…”
Section: From Localized To Vacillating Convectionmentioning
confidence: 99%